2014
DOI: 10.1539/joh.14-0012-oa
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Impact of Occupational Exposure of Pharmaceutical Workers on the Development of Antimicrobial Drug Resistance

Abstract: of nasal fluids, mucuses and stools, respectively. Results: All the isolated species of bacteria exhibited significant enhancement of the degree of MDR in pharmaceutical workers compared with non-pharmaceutical subjects. Workers with a longer working history had greater degree of antibiotic resistance and vice versa. It can be certainly considered that the exposure of pharmaceutical workers to antibiotic agents resulted in a high incidence of multidrug resistance. Conclusions: Effective steps should be taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…multi-drug resistance compared with non-pharmaceutical subjects. 16 In this study, the percentage of penicillin resistance was nearly 93% in pharmaceutical workers and 71.4% among food industry workers, indicating a high level of resistance in both groups. A similar result were reported by study of Sarker et al 16 in Bangladesh that showed 100% resistance to amoxicillin for pharmaceutical workers and 66.7% resistance for non-pharmaceutical workers.…”
Section: Penicillin Concentration and Twamentioning
confidence: 47%
See 2 more Smart Citations
“…multi-drug resistance compared with non-pharmaceutical subjects. 16 In this study, the percentage of penicillin resistance was nearly 93% in pharmaceutical workers and 71.4% among food industry workers, indicating a high level of resistance in both groups. A similar result were reported by study of Sarker et al 16 in Bangladesh that showed 100% resistance to amoxicillin for pharmaceutical workers and 66.7% resistance for non-pharmaceutical workers.…”
Section: Penicillin Concentration and Twamentioning
confidence: 47%
“…16 In this study, the percentage of penicillin resistance was nearly 93% in pharmaceutical workers and 71.4% among food industry workers, indicating a high level of resistance in both groups. A similar result were reported by study of Sarker et al 16 in Bangladesh that showed 100% resistance to amoxicillin for pharmaceutical workers and 66.7% resistance for non-pharmaceutical workers. A surveillance by WHO on drug resistance has reported 33.9% S. pneumoniae resistance or non-susceptibility to penicillin in Iran, which is a much lower resistance level in comparison with the prevalence reported in this study.…”
Section: Penicillin Concentration and Twamentioning
confidence: 47%
See 1 more Smart Citation
“…Although most of the products stated the withdrawal time, the depletion of antimicrobials in different fish species varied when treating bacterial diseases; provision of general information without indicating specific fish species is not sufficient to help farmers to manage the application of antimicrobial products and to avoid their overuse (Xu, Zhu, Wang, Deng, & Zhang, ). Additionally, none of the products stated information on how to protect the health of farmers when handling antimicrobial products, for example, exposure to antimicrobials, especially to injuries, might lead to skin allergy, organ‐specific reactions and the development of antimicrobial resistance (Sarker et al, ; Thong, ).…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were inoculated in Muller-Hinton Agar medium which was previously prepared with an addition of pesticide. Inhibition zone was measured in millimeter after an incubation of 24 h (Sarker et al, 2014). In this study, four antibiotics were used.…”
Section: Estimation Of Extracted Exopolysaccharide By Spectrophotometrymentioning
confidence: 99%